Increased sarcolemmal Na+/H+ exchange activity in hypertrophied myocytes from dogs with chronic atrioventricular block - van Borren, Marcel; Vos, Marc; Houtman, Marien; Antoons, Gudrun; Ravesloot, Jan H. (Frontiers in Physiology, 2013)
Dogs with compensated biventricular hypertrophy due to chronic atrioventricular block (cAVB), are more susceptible to develop drug-induced Torsade-de-Pointes arrhythmias and sudden cardiac death. It has been suggested that the increased Na+ influx in hypertrophied cAVB ventricular myocytes contribute to these lethal arrhythmias. The increased Na+ influx was not mediated by Na+ channels, in fact the Na+ current proved reduced in cAVB myocytes. Here we tested the hypothesis that increased activity of the Na+/H+ exchanger type 1 (NHE-1), commonly observed in hypertrophic hearts, causes the elevated Na+ influx. Cardiac acid-base transport was studied with a pH-sensitive fluorescent dye in ventricular myocytes isolated from control and hypertrophied cAVB hearts; the H+ equivalent flux through NHE-1, Na+-HCO3- cotransport (NBC), Cl-/OH- exchange (CHE) and Cl-/HCO3- exchange (AE) were determined and normalized per liter cell water and corrected for surface-to-volume ratio. In cAVB, sarcolemmal NHE-1 flux was increased by 65±6.3% in the pHi interval 6.3-7.2 and NBC, AE and CHE fluxes remained unchanged. Accordingly, at steady-state intracellular pH the total sarcolemmal Na+ influx by NHE-1+NBC increased from 8.5±1.5 amol/μm2/min in normal myocytes to 15±2.4 amol/μm2/min in hypertrophied cAVB myocytes. We conclude that compensated cardiac hypertrophy in cAVB dogs is accompanied with an increased sarcolemmal NHE-1 activity. This in conjunction with unchanged activity of the other acid-base transporters will raise the intracellular Na+ in hypertrophied cAVB myocytes.